PENINGKATAN RESOLUSI CITRA DENGAN MENGGUNAKAN TRANSFORMASI WAVELET - Wenda Kartika; Dyah Erny Herwindiati (Jurnal Ilmu Komputer dan Sistem Informasi, 2015)
In this paper, we propose a satellite image resolution enhancement technique based on wavelet transform by by combining the panchromatic image (PAN) with multispectral image (MS). To make the range of the coefficients consistent with the range of the PAN approximation coefficients under the same resolution, bilinear transform of the MS approximate image coefficient is computed before the merging. To improve image resolution used Wavelet Transform. Wavelet transform used is the Haar wavelet, Daubechies 2, Daubechies 3, Daubechies 4, Symlets 2, Symlets 3, Symlets 4, Symlets 6, Coiflets 1, and Coiflets 2. For analyzing the performance of the image resolution enhancement, we use performance evaluation. In the test results obtained that the most appropriate method for improving image resolution is Daubechies 2 to experiment without the use of resampling and Symlet 6 to experiment with the use of resampling. Key wordsBilinear Transform, Remote Sensing, Performance Evaluation, Wavelet Transform.